Phytochemistry and Biological Activities of Essential Oils from Six Aromatic Medicinal Plants with Cosmetic Properties - Atika Ailli; Nadia Handaq; Hanane Touijer; Aman Allah Gourich; Aziz Drioiche; Khalid Zibouh; Brahim Eddamsyry; Fadoua El Makhoukhi; Aicha Mouradi; Yousef A. Bin Jardan; Mohammed Bourhia; Abdelhakim Elomri; et al. (MDPI AG, 2023)
In this work, the chemical composition and antioxidant and antimicrobial activities of the essential oils (EOs) of six species-Laurus nobilis, Chamaemelum nobile, Citrus aurantium, Pistacia lentiscus, Cedrus atlantica, and Rosa damascena-have been studied. Phytochemical screening of these plants revealed the presence of primary metabolites, namely, lipids, proteins, reducing sugars, and polysaccharides, and also secondary metabolites such as tannins, flavonoids, and mucilages. The essential oils were extracted by hydrodistillation in a Clevenger-type apparatus. The yields are between 0.06 and 4.78% (mL/100 g). The analysis of the chemical composition carried out by GC-MS showed the presence of 30 to 35 compounds and represent between 99.97% and 100% of the total composition of EOs, with a variation in the chemical composition detected at the level of the majority compounds between these species. Indeed, in the EO of Laurus nobilis, 1,8-cineole (36.58%) is the major component. In Chamaemelum nobile EO, the most abundant compound is angelylangelate (41.79%). The EO of Citrus aurantium is rich in linalool (29.01%). The EO of Pistacia lentiscus is dominated by 3-methylpentylangelate (27.83%). The main compound of Cedrus atlantica is β-himachalene (40.19%), while the EO of Rosa damascenaa flowers is rich in n-nonadecane (44.89%). The analysis of the similarity between the EOs of the plants studied by ACH and ACP showed that the chemical composition of the EOs makes it possible to separate these plants into three groups: the first represented by Chamaemelum nobile, because it is rich in oxygenated monoterpenes, the second defined Cedrus atlantica and Rosa damascena, which are rich in sesquiterpenes, and the third gathers Pistacia lentiscus, Laurus nobilis and Citrus aurantium, which are composed of oxygenated sesquiterpenes and monoterpenes (these three species are very close). The study of the antioxidant activity showed that all the EOs tested have a high capacity for scavenging free radicals from DPPH. The EOs of Laurus nobilis and Pistacia lentiscus showed the highest activity, 76.84% and 71.53%, respectively, followed by Cedrus atlantica EO (62.38%) and Chamaemelum nobile (47.98%) then Citrus aurantium EO (14.70%). Antimicrobial activity EO was tested against eight bacterial strains and eight fungal strains; the results showed that EOs exhibit significant bactericidal and fungicidal activities against all the microorganisms tested, of which the MICs of the bacterial strains start with 5 mg/mL, while the MICs of the fungal strains are between 0.60 mg/mL and 5 mg/mL. Thus, these EOs rich in antimicrobial and antioxidant components can serve as a natural alternative; this confirms their use as additives in cosmetics.